Viabilidade econômica da utilização de biogás produzido em aterros sanitários para a geração de energia elétrica - Cavaler, Viviane (2022)
Faced with the increase in population and the disorderly growth of cities, the generation and final destination of urban solid waste is a problem that has gradually worsened, becoming a threat to public health. Sanitary landfills are one of the most common alternatives for the disposal of urban solid waste. They generate biogas as a by-product, which has a high potential for energy production. However, it is necessary to evaluate the economic feasibility for each situation, in terms of compensation. Therefore, the objective of this study was to verify the economic feasibility of installing the energy generation system within landfills in cities that have a population of 30 thousand, 100 thousand and 250 thousand inhabitants, in order to stimulate the usage of biogas as a source of renewable energy. On this account, twelve different scenarios were considered, the first three of which contemplated the municipal landfill of Cascavel - PR and the utilization of the generated energy for compensation alongside the Companhia Paranaense de Energia, from 20%, 50% and 80% of the capacity of the electric power generation. On the other hand, the other scenarios considered the utilization of electric energy for compensation alongside the local concessionaire, considering municipalities that have a population of 30 thousand, 100 thousand and 250 thousand inhabitants, evaluating 20%, 50% and 80% of the generation capacity. For all cases, the generation of urban solid waste was considered, in line with the average of the masses per capita according to the population ranges of the National Sanitation Information System. The biogas generated within the landfills was calculated by analyzing the electricity bills of the Cascavel Municipal landfill from January 2019 to January 2020, and extrapolated to the other scenarios, considering that the potential for biogas generation corresponds to 75.78 m3CH4 ton-1 and that one cubic meter of biogas is equivalent to 1.43 kWh of electricity. It was presumed that the price per MWh of generated energy was R$ 0.5075, based on the tariff group to which the generation unit belongs. In addition, in order to estimate the power needed to be installed, it was considered that the system would work 15 hours a day, 360 days a year. The feasibility of the enterprise was calculated by using the Net Present Value, the Internal Rate of Return and the discounted Payback. Comparing these economic indicators and the analyzes that were carried out, it can be concluded that of the 12 scenarios evaluated, only 2 were not viable. The scenarios that considered the utilization of 20% and 50% of the energy utilization capacity in municipalities with a population of 30 thousand inhabitants did not prove to be viable, emphasizing that the greater the number of inhabitants and the utilization of the generated biogas, the greater the NPV and, consequently, the feasibility of the enterprise. All the scenarios analyzed for the municipality of Cascavel and the scenarios that considered the utilization of 50% and 80% of the generation capacity in municipalities with a population of 250 thousand inhabitants presented the same payback: 4 years. The scenario that presented the lowest payback: 3 years, considered the utilization of 80% of the energy generation capacity in municipalities that have a population of 100 thousand inhabitants. On the other hand, the scenarios that presented the longest payback time, 14 and 15 years, respectively, considered the utilization of 20% and 80% of energy in municipalities with a population of 100 thousand and 30 thousand inhabitants. The scenarios that considered 20% and 50% of the utilization of energy generation in municipalities with a population of 250 and 100 thousand inhabitants, respectively, presented a payback of 5 years. The assessment of the feasibility of installing the energy viii generation system from biogas in sanitary landfills in municipalities that have a population of 30 thousand, 100 thousand and 250 thousand inhabitants allowed the elaboration of equations that can help to estimate the best scenario, within the idiosyncrasies of each city, in order to contribute when it comes to the public administration understanding the importance of the correct destination of urban solid waste and utilizing it for the generation of clean and sustainable energy.